Description of bone health in adolescents and young persons with Klinefelter syndrome - results from a pilot study - Julia Spiekermann; Jakob Höppner; Eliena Ibnukhsein; Kathrin Sinningen; Beatrice Hanusch; Cordula Kiewert; Heide Siggelkow; Corinna Grasemann (SpringerOpen, 2024)
Abstract Background In adults with Klinefelter syndrome (KS), impaired bone health with reduced bone mineral density (BMD) has been described even in the presence of testosterone replacement therapy. The aim of the present study was to characterize bone health in young patients with KS. Patients and methods 20 participants aged 16.10 ± 4.28 years with KS (7 with testosterone replacement therapy) were included in the KliBONE study (DRKS 00024870). Medical history, clinical, radiographic and biochemical parameters of bone health and metabolism were obtained. Radiographic bone health index (BHI) was assessed via automated digital X-ray radiogrammetry of the left hand or via dual energy X-ray absorptiometry (DXA) of the lumbar spine and left femur in participants ≥ 16 years. Peripheral blood mononuclear cells were differentiated into osteoclasts and quantified in 7 participants and 7 healthy controls. Results Mean BHI SDS was − 1.42 ± 1.22 and mean BMD z-score at the lumbar vertebrae (L1-4) was − 0.92 ± 1.00. 25-OH-vitamin D levels < 20 ng/ml were detected in 8/20. Other parameters of bone metabolism (bone-specific alkaline phosphatase, PTH, ß-crosslaps and osteocalcin) were within age-appropriate reference ranges. Serum leptin SDS was elevated (mean 2.15 ± 1.19). The number of osteoclasts in participants with KS did not differ from that of controls. Conclusion BHI SDS and BMD z-scores were lower than expected in young individuals with KS despite age-appropriate bone turnover markers and no apparent pathology in osteoclast differentiation. The cause of the early-onset bone phenotype requires further investigation.